A duch jego był napięty jak łuk - Stankiewicz, Lucyna (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
The author of this article discusses particular fields of activity of Appius Claudius the Blind, the first individualised figure in Latin literature. This citizen of Rome who lived at the turn of the 4th and 3rd century B.C. became famous as an outstanding politician, reformer and orator.
And his spirit was as taut as a bow
Keywords: Appius Claudius Caecus; elogium; sententia